Combination of Chemical Coagulation and Biological Treatment of Cellulosic Effluents - Shaaban Ghodbanan (آب و فاضلاب, 2005)
There are various methods for treatment and decolorization of industrial wastewater such as: chemical oxidation, biological treatment, electrochemical technologies, ion exchange, adsorption process, membrane process, chemical reduction, coagulation and flocculation Among these methods chemical coagulation and biological treatment are common methods of waste water treatment which are used as single or combined regarding the level of effluent pollution and also its characteristics. In this research, the performance of combined methods in decontamination of pulp mill effluent have been investigated. As a result combination of these methods is a suitable system for treatment of colored effluent discharged from pulp industries.